A robust controller design method and stability analysis of an underactuated underwater vehicle - Chin, Cheng Siong; Lau, Micheal Wai Shing; Low, Eicher; Seet, Gerald Gim Lee (Zielona Góra: Uniwersytet Zielonogórski)
The problem of designing a stabilizing feedback controller for an underactuated system is a challenging one since a nonlinear system is not stabilizable by a smooth static state feedback law. A necessary condition for the asymptotical stabilization of an underactuated vehicle to a single equilibrium is that its gravitational field has nonzero elements corresponding to unactuated dynamics. However, global asymptotical stability (GAS) cannot be guaranteed.
Keywords: underwater vehicle; underactuated; stabilizable; robust controller; simulation